2001
DOI: 10.1046/j.1365-2028.2001.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate prey and predatory behaviour of the omnivorous African tortoise Kinixys spekii

Abstract: Invertebrates form an important part of the diet in the omnivorous African tortoises of the genus Kinixys. Millipede prey of Kinixys spekii in Zimbabwe had a mean volume of 0.9 ml, and made up 64.7% of invertebrate food by volume; beetles made up most of the remainder and had a mean volume of 1.4 ml. The mean mass of invertebrate prey was 0.19% of tortoise mass, a similar value of relative prey mass to many insectivorous lizards. Tortoises preferentially attacked moving millipedes at or just behind the head, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
0
12
1
1
Order By: Relevance
“…K. spekii, a tortoise in Zimbabwe, eats many millipedes, usually first biting off the heads, but if the millipedes coil, the tortoise bites at the outermost rings. Chemical defenses appeared to be without effect (Hailey et al, 2001). Eisner et al (1978) found that if frogs or toads captured millipedes with their tongues and swallowed them immediately, the millipedes' secretions had no effect.…”
Section: Vertebrate Predatorsmentioning
confidence: 97%
See 1 more Smart Citation
“…K. spekii, a tortoise in Zimbabwe, eats many millipedes, usually first biting off the heads, but if the millipedes coil, the tortoise bites at the outermost rings. Chemical defenses appeared to be without effect (Hailey et al, 2001). Eisner et al (1978) found that if frogs or toads captured millipedes with their tongues and swallowed them immediately, the millipedes' secretions had no effect.…”
Section: Vertebrate Predatorsmentioning
confidence: 97%
“…Niponia nodulosa (Polydesmida, Cryptodesmidae) is not cyanogenic as are the majority of polydesmidans, but produces 1-octen-3-ol and geosmin, neither of which repel ants, but which may be directed at other predators (Omura et al, 2002a). The possum Didelphis albiventris reacts somewhat aversely to the odors of millipedes, but eats them anyway (Santori, 1998), and a tortoise, Kinixys spekii, eats large spirostreptids without any ill effects (Hailey et al, 2001). Millipede secretions may not always work if they are specialized to repel only certain predators.…”
Section: Targets Of Secretionsmentioning
confidence: 99%
“…The range and relative quantities of food types consumed by omnivores in nature varies among related species (birds, O'Donnell and Dilks 1994;rodents, Ellis et al 1998), populations or environments (Wilson and Bradtke 1999), and conspecific individuals within a population (e.g., sexual differences, Hailey et al 2001;immigrants vs. residents, Tardiff and Gray 1978). There are limited data to address this question at present.…”
Section: Ecological Consequences Of Food Mixingmentioning
confidence: 99%
“…Yet, it is clear that food mixing by one omnivore cannot be assumed to be ecologically equivalent to food mixing by another. The range and relative quantities of food types consumed by omnivores in nature varies among related species (birds, O'Donnell and Dilks 1994;rodents, Ellis et al 1998), populations or environments (Wilson and Bradtke 1999), and conspecific individuals within a population (e.g., sexual differences, Hailey et al 2001;immigrants vs. residents, Tardiff and Gray 1978). Furthermore, we think the precise factors that govern variation in food mixing and food selection may determine their ecological consequences.…”
Section: Ecological Consequences Of Food Mixingmentioning
confidence: 99%
“…RPM varies in complex ways both intraspecifically, e.g., as a function of predator sex and age, location and season (Mushinsky et al 1982;Arnold 1993;Lind and Welsh 1994;Schindler et al 1997;Dorner and Wagner 2003;Kingsley-Smith et al 2003;Fenech et al 2004;Paill 2004;Vincent et al 2004) and interspecifically, e.g., between major clades (Magnusson et al 1985;Mushinsky 1987;Vitt and Decarvalho 1995;Vitt et al 1997;Perry and Pianka 1997;Bethea et al 2004;Radloff and Du Toit 2004). Across a remarkably wide phylogenetic diversity of taxa, RPM has been shown to affect not only the nutritional benefit obtainable, but also the energetic and risk-associated costs of prey-handling (Griffiths 1980;Mori 1991;Munk 1992;Cruz-Neto et al 2001;Hailey et al 2001;Zaidan and Beaupre 2003;Johansson et al 2004).…”
Section: Introductionmentioning
confidence: 97%